(untitled) (KULT_online, 2024)
In this volume, Classen brings together 19 case studies of economic, political, technological interconnectedness during the Middle Ages and Early Modernity. It is a contribution to the ‘global turn’ in history: challenging contemporary assumptions that globalism is very recent, but also the entrenched view of the Eurocentrism of previous times, giving the essays urgent relevance. Further, written by a combination of early-career researchers and established scholars, the book itself provides an excellent example of global, interdisciplinary scientific research.